Enteropathy-associated t-cell lymphoma presenting as refractory cutaneous ulcers in a 28-year-old male: a case report and literature review - Zhao, Dejie; Li, Quanlin; Liu, Dan; Xu, Jie; Liu, Zheng; Zhao, Yanan; Cheng, Zhixin; Liu, Ming (Frontiers in Oncology, 2025)
BackgroundEnteropathy associated T-cell lymphoma (EATL) is a rare and aggressive subtype of peripheral T-cell lymphoma, most commonly associated with celiac disease (CD). It typically presents with gastrointestinal symptoms and carries a poor prognosis. Cutaneous involvement as the initial manifestation, particularly in the form of refractory skin ulcers in young patients, is rare.Case summaryWe report a 28-year-old male who presented with a one-year history of refractory, non-healing ulcers on the right foot and several years of chronic diarrhea, initially misdiagnosed and treated as a chronic infection in April 2019. Despite multiple antibiotic regimens, surgical debridement, and immunosuppressive therapy, the lesions progressed symmetrically to involve the right hand and left thigh. The patient underwent amputation of the right lower limb and right hand in October 2020. One month later, the patient developed acute peritonitis secondary to jejunal perforation. Laparotomy revealed a transmural tumor mass, and histopathological and immunohistochemical analyses confirmed EATL (CD3+/CD103+/TIA-1+/GRANB+, CD5-/CD8-, Ki-67 ~70%). The patient died of multiorgan failure three weeks postoperatively in December 2020.ConclusionThis case underscores that EATL may manifest with widespread cutaneous ulcers more than one year before the onset of severe gastrointestinal symptoms. In patients with chronic diarrhea and refractory skin ulcers, celiac disease should be excluded, while cutaneous lesions should be recognized as potential paraneoplastic manifestations of an underlying lymphoma. Diagnostic delays—driven by anchoring bias and insufficient tissue sampling—are critical contributors to advanced disease at presentation and poor clinical outcomes.